(untitled) (American Journal of Islam and Society, 2006)
The First Annual Muslim Peacebuilding, Justice, and Interfaith Dialogue was held on 28-30 April 2006. Sponsored by the Salam Institute for Peace and Justice (SIPJ) and the Islamic Society of North America (ISNA), it was made possible through a Conflict Transformation Grant, in part with the Fuller Theological Seminary, and the generous support provided by the Mohammed Said Farsi Chair of Islamic Peace at American University. The conference was opened by Mohammed Abu-Nimer (SIPJ) and Louay Safi (ISNA). Abu-Nimer explained that this event was being held to “systematically think about the Islamic perspectives of peacebuilding, conflict resolution, and interfaith dialogue, and to attempt to bring it into the American public context.” Safi mentioned that “it is crucial that we learn how to prevent and resolve these inevitable conflicts.” After these opening remarks, the panel sessions began. Panel 1, “Peace through Development: Experiences from Muslim Communities and the Muslim World,” discussed the effect of development practices in Muslim communities on the peace and sustainability of both these communities themselves and their outside interactions. Kathleen Meilahn spoke about the United States’ inability to create a sustainable peace in Iraq due to its lack of cultural and religious understanding. She was followed by Ayse Kadayifici-Orellana, who presented the SIPJ’s study on Muslim Peacebuilders in Africa and the Balkans. Her major findings included the use of and the need to expand the concept of tawhid (that all of creation emanates from God) and therefore must understand unity through plurality. Putut Widjanarko’s presentation focused on the Muslim community’s contribution to reducing ethnic differences within Islam. Panel 2, “Intra-Muslim Dialogue,” focused on the need for intra-faith dialogue among Muslims. The presenters pinpointed the Sunni-Shi`ah spilt, differences between converted Muslims and born Muslims, and ideological ...